2019
DOI: 10.1098/rsos.190738
|View full text |Cite
|
Sign up to set email alerts
|

Research practices and statistical reporting quality in 250 economic psychology master's theses: a meta-research investigation

Abstract: The replicability of research findings has recently been disputed across multiple scientific disciplines. In constructive reaction, the research culture in psychology is facing fundamental changes, but investigations of research practices that led to these improvements have almost exclusively focused on academic researchers. By contrast, we investigated the statistical reporting quality and selected indicators of questionable research practices (QRPs) in psychology students' master's theses. In a total of 250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 82 publications
1
13
1
Order By: Relevance
“…We intended to assess the replication results by comparing effect sizes between the original and replication studies (see , but the original results in the paper by were not reported in sufficient detail to allow for such comparisons, which further points to the importance of complete statistical reporting in scientific articles (see Bakker & Wicherts, 2011;Olsen et al, 2019). Nonetheless, (in Supplemental Materials) we present effect size comparisons between the replication and original studies, where possible.…”
Section: Resultsmentioning
confidence: 99%
“…We intended to assess the replication results by comparing effect sizes between the original and replication studies (see , but the original results in the paper by were not reported in sufficient detail to allow for such comparisons, which further points to the importance of complete statistical reporting in scientific articles (see Bakker & Wicherts, 2011;Olsen et al, 2019). Nonetheless, (in Supplemental Materials) we present effect size comparisons between the replication and original studies, where possible.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, theses differ from published manuscripts in many aspects that may be relevant for their review and evaluation. For example, previous research showed that theses report effect sizes more frequently than published manuscripts (Augusteijn et al, 2022;Fritz et al, 2013;Krishna & Peter, 2018), on average use larger samples (Olsen, et al, 2019), and conduct a priori power analysis more often (Krishna & Peter, 2018;Kühberger et al, 2014). These differences could also indicate that students and researchers consider different aspects in assessing the quality of these manuscripts.…”
Section: Review In Educationmentioning
confidence: 98%
“…For example, the Framework of Open and Reproducible Research Training (FORRT; www.forrt.org) includes preregistration as one of the six pillars of effective reproducibility training, including at the undergraduate level. Others have suggested that “most study programmes should offer easy ways of implementing preregistration in empirical research seminars” (Olson et al, 2019) because of the potential for preregistration to promote “critical reflections of research practices” and improve students’ statistics literacy (Olson et al, 2019). As Pownall (2020b) also argued, the process of embedding preregistration of undergraduate dissertations largely complements current practices in dissertation supervision.…”
Section: The Value Of Preregistrationmentioning
confidence: 99%